On the formation of the first quasars - Valiante, Rosa; Agarwal, Bhaskar (Publications of the Astronomical Society of Australia, 2017)
Observations of the most luminous quasars at redshift z > 6 reveal the existence of numerous supermasssive black holes (>199 M⊙) already in place about 12 billion years ago. In addition, the interstellar medium of the galaxies hosting these black holes are observed to be chemically mature systems, with metallicities (Z > Z⊙) and dust masses (>108 M⊙) similar to that of more evolved, local galaxies. The connection between the rapid growth of the first supermassive black holes and the fast chemical evolution of the host galaxy is one of the most puzzling issues for theoretical models. Here, we review state-of-the-art theoretical models that focus on this problem with particular emphasis on the conditions that lead to the formation of quasar seeds and their subsequent evolution at z ⩾ 6.
Gesehen am 25.10.2018